ROCK inhibitors modulate the physical properties and adipogenesis of 3D spheroids of human orbital fibroblasts in different manners. Issue 10 (26th July 2021) - Hikage, Fumihito; Ichioka, Hanae; Watanabe, Megumi; Umetsu, Araya; Ohguro, Hiroshi; Ida, Yosuke
Abstract: To elucidate the pharmacological effects of Rho‐associated coiled‐coil containing protein kinase inhibitors (ROCK‐is), ripasudil (Rip), Y27632, and KD025, on human orbital fatty tissue, the human orbital fibroblasts (HOFs) were three‐dimensional (3D) cultured for 12 days. The effects of ROCK‐is on the physical properties of the 3D‐cultured HOF spheroids, including their sizes and physical stiffness, their adipogenesis by lipid staining, and the mRNA expression of adipogenesis‐related genes, PPARγ and AP2, and extracellular matrix (ECM) including collagen (COL) 1, 4, and 6, and fibronectin were analyzed. A significant increase in the sizes, physical stiffness, lipid staining, and mRNA expression of adipogenesis‐related genes, COL4 and COL6, and a decrease in COL1 expression were observed with adipogenesis (DIF+). In the presence of ROCK‐is, such DIF+‐induced effects were differently modulated as follows: (1) the sizes were not affected or significantly enhanced by Rip, Y27632, or KD025, (2) the physical stiffness was significantly decreased in Rip and Y27632, but was substantially increased in KD025, (3) the lipid staining was further enhanced or significantly suppressed by Rip, Y27632, or KD025, and both PPARγ and AP2 expression were significantly downregulated or upregulated by KD025 or Rip, and (4) Rip upregulated the expression of COL4, Y27632 upregulated the expression of COL1, COL4, and COL6, and KD025 upregulated the expression of COL1 and COL4 . This study indicates that ROCK‐is significantly and differently modulate physical properties of the 3D HOF spheroids as well as their adipogenesis.